2007
DOI: 10.1021/la0632171
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Adsorption of an Oppositely Charged Polymer−Surfactant Mixture at the Air−Water Interface:  Poly(dimethyldiallylammonium chloride) and Sodium Dodecyl Sulfate

Abstract: The dynamic adsorption behavior of mixtures of the cationic polymer poly(dimethyldiallylammonium chloride) [poly(dmdaac)] and the anionic surfactant sodium dodecyl sulfate (SDS) has been studied at the expanding liquid surface of an overflowing cylinder. A combination of ellipsometry and external reflection Fourier transform infrared spectroscopy was used to measure the adsorbed amounts of poly(dmdaac) and SDS as a function of the bulk surfactant concentration for various polymer concentrations in the range 0-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 64 publications
1
61
0
Order By: Relevance
“…If these species also require greater amounts of surfactant for precipitation, which is plausible, this would cause the observed discrepancy. Support for this comes from the dynamic experiments of Campbell et al 16 Campbell et al 16 used the overflowing cylinder to study the surface of PDMDAAC−SDS−NaCl on a 1 s time scale. They found a constant PE−S ratio in the adsorbed layer over the whole concentration range up to the equivalence point and a broad dip down to zero adsorption at the equivalence point.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If these species also require greater amounts of surfactant for precipitation, which is plausible, this would cause the observed discrepancy. Support for this comes from the dynamic experiments of Campbell et al 16 Campbell et al 16 used the overflowing cylinder to study the surface of PDMDAAC−SDS−NaCl on a 1 s time scale. They found a constant PE−S ratio in the adsorbed layer over the whole concentration range up to the equivalence point and a broad dip down to zero adsorption at the equivalence point.…”
Section: ■ Discussionmentioning
confidence: 99%
“…45 The interest in such systems is the evolution of wetting of the surface near the upper consolute temperature, but we are here interested only in the simpler behavior. Wetting is governed by Antonow's rule, which is that the interfacial tensions of the three potential interfaces in the two liquid phase + vapor system obey the relation (16) where γ denotes air and the αγ interface is taken to have the highest interfacial tension and α is the upper bulk liquid phase. The rule requires that at equilibrium the αγ surface is coated by a wetting film of the lower surface energy β phase, 46 but if it is not obeyed, a drop of β phase forms only a lens on the α phase.…”
Section: Surfactant Systemsmentioning
confidence: 99%
“…Campbell et al [45] studied the kinetics of adsorption of these mixtures in an overflowing cylinder (OFC), which is a device for generating a continuously expanding flat liquid surface under steadystate conditions [46]. The surface of the OFC expands uniformly with a strain rate, θ, in the range of 0.5 -5 s -1 ; the equivalent surface age is given approximately by (2θ) -1 .…”
Section: Dynamics Of Adsorption In Polymer/surfactant Mixturesmentioning
confidence: 99%
“…It was usually observed that at certain surfactant concentrations such interaction leads to precipitation of a polymersurfactant complex. This precipitation was characterized for various oppositely charged polyelectrolyte-surfactant systems [12][13][14][15][16][17]. To prevent or reduce the phase separation in such systems, the addition of a salt is often required [18,19].…”
Section: Introductionmentioning
confidence: 99%